The role of rivers and streams in the migration of alien plants into the Polish Carpathians - Zając, Adam; Tokarska-Guzik, Barbara; Zając, Maria (Biodiversity: Research and Conservation, 2012)
The Carpathians are among the regions of Poland that are generally less susceptible to invasive alien plants. The factor limiting the spread of the species of this group is, above all, the mountain climate. Even species originating from other mountain regions, e.g. the Himalayan Impatiens glandulifera, have their localities only at low elevations, in the Carpathian foothills. In most cases, alien plant species migrate into the Carpathians from the lowlands. The river valleys provide the migration corridors used by alien species in the course of their progress into new territories of the upper mountain localities. The situation along some mountain rivers, where invasive alien species dominate the native vegetation, is dramatic. Their spread is facilitated not only by easy diaspore transport but also by some anthropogenic factors, such as, river engineering and the transformation of riparian habitats and progressing devastation. Currently, we can observe some invasive alien plants "in statu nascendi", developing a new, secondary range in the Carpathians (e.g. Chaerophyllum aureum) or at the foothills, along the Wisła (Vistula) and San river valleys (e.g. Eragrostis albensis). For some species, cities were the destination for the first stage of future migration, e.g. Acer negundo. In the Carpathians, where many national parks and nature reserves are located, the continuous monitoring of the spread of invasive alien plants should be one of the principal activities of botanists.